Biology and clinical relevance of follicular cytotoxic T cells - Lv, Yuqi; Ricard, Laure; Gaugler, Béatrice; Huang, He; Ye, Yishan (Frontiers in Immunology, 2022)
Follicular cytotoxic T (Tfc) cells are a newly identified subset of CD8+ T cells enriched in B cell follicles and their surroundings, which integrate multiple functions such as killing, memory, supporting and regulation. Tfc cells share similarities with follicular helper T (Tfh) cells, conventional cytotoxic CD8+ T （Tc ）cells and follicular regulatory T (Tfr) cells, while they express distinct transcription factors, phenotype, and perform different functions. With the participation of cytokines and cell-cell interactions, Tfc cells modulate Tfh cells and B cells and play an essential role in regulating humoral immunity. Furthermore, Tfc cells have been found to change in their frequencies and functions during the occurrence and progression of chronic infections, immune-mediated diseases and cancers. Strategies targeting Tfc cells are under investigation, bringing novel insights into control of these diseases. We summarize the characteristics of Tfc cells, and introduce the roles and potential targeting modalities of Tfc cells in different diseases.